Bake n' Joy Incorporated a production systems study - Catanghal, Elena V. (College of Engineering, 1992)
A study on the production systems of a food firm, Bake n' Joy Incorporated was done for the purpose of providing the company with a documentation of its present set-up as well as analyzing how the system should effectively work. Basically the study wishes to identify problem areas with regards to Plant Layout, Organizational Set-up, Production Planning and Control (Forecasting, Capacity Planning and Inventory Management) as well as other support systems such as Quality Control and Ergonomic considerations. In this manner, methods and processes can be designed and developed to work more efficiently thereby coming up with a high productivity performance. Information gathering was done by means of interviews and observations during plant visits as well as data sheets provided by the company. Because of the varied production of goods,only one type of bread, the Pullman loaf, was the focus of the study since it constituted 80% of total production. The present production process, from mixing to packing, work flow, tools and equipment used in production were documented. Also, demand patterns were necessary information so that a proper forecasting model could be developed since the product involved is a perishable item. Consequently machine and labor capacity as well as inventory control were identified and analyzed. Pertinent to the system was the Quality Control procedure employed by the company which was documented and analyzed. After problem areas were identified, a set of criteria was developed as a basis for evaluating alternatives to arrive at the best possible solution. These set of recommendations would be presented to the management which hopefully could be considered by the company.